Mutations in orbit/mast reveal that the central spindle is comprised of two microtubule populations, those that initiate cleavage and those that propagate furrow ingression. - Inoue, Y.H.; Savoian, M.S.; Suzuki, T.; Mathe, E.; Yamamoto, M.T.; Glover, D.M. (Journal of Cell Biology, 2004)
We address the relative roles of astral and central spindle microtubules (MTs) in cytokinesis of Drosophila melanogaster primary spermatocytes. Time-lapse imaging studies reveal that the central spindle is comprised of two MT populations, "interior" central spindle MTs found within the spindle envelope and "peripheral" astral MTs that probe the cytoplasm and initiate cleavage furrows where they contact the cortex and form overlapping bundles. The MT-associated protein Orbit/Mast/CLASP concentrates on interior rather than peripheral central spindle MTs. Interior MTs are preferentially affected in hypomorphic orbit mutants, and consequently the interior central spindle fails to form or is unstable. In contrast, peripheral MTs still probe the cortex and form regions of overlap that recruit the Pav-KLP motor and Aurora B kinase. orbit mutants have disorganized or incomplete anillin and actin rings, and although cleavage furrows initiate, they ultimately regress. Our work identifies a new function for Orbit/Mast/CLASP and identifies a novel MT population involved in cleavage furrow initiation.